2002
DOI: 10.1021/ja027955x
|View full text |Cite
|
Sign up to set email alerts
|

DNA Sequence Context and Multiplex Hybridization Reactions:  Melting Studies of Heteromorphic Duplex DNA Complexes

Abstract: Heteromorphic hybrid duplex DNA complexes are duplex states, other than perfectly matched duplexes, that can form when single strands comprising several different perfectly matched duplexes are simultaneously present in solution. Such cross-hybridization "side reactions" are of particular nuisance in multiplex reaction schemes, where many strands are designed to hybridize in parallel fashion with only their corresponding perfect complement strand. Relative to the perfect match duplexes, the sequence dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…These parameters are intended for calculating the thermodynamic effect of a single base pair mismatch. Complexities exist due to multiple mismatches and mismatch context within a duplex (33,34). Due to these issues, a conservative approach was implemented for dealing with mismatched base pairing.…”
Section: Resultsmentioning
confidence: 99%
“…These parameters are intended for calculating the thermodynamic effect of a single base pair mismatch. Complexities exist due to multiple mismatches and mismatch context within a duplex (33,34). Due to these issues, a conservative approach was implemented for dealing with mismatched base pairing.…”
Section: Resultsmentioning
confidence: 99%
“…Exceptions are studies of solutions containing a single species of a linear or circular self-complementary single strand for the purpose of evaluating DNA sequence-dependent stability parameters, and examining intramolecular hairpin stability (43)(44)(45), and studies performed for the purpose of investigating the thermodynamic parameters of single basepair mismatches (1,9,46), bulged loops (47)(48)(49), or multiple strand mixtures, such as triplexes and quadruplex (50). Melting studies of mixtures of more than two strands in solution, which can form both perfect match and mismatch duplex complexes, have suggested that sequence-dependent interactions in tandem mismatches might contribute to the stability of mismatch hybrid duplex complexes (51). For this and other reasons described herein, when multiple strands meant to form perfectly matched duplexes are present together in a reaction mix, it cannot be presumed that each pair of strands will form the appropriate duplex, exclusively, in the same way they would in isolation, in the absence of the influence from other single strands (and duplexes).…”
Section: Introductionmentioning
confidence: 99%
“…Given that they are driven by free energy reductions that usually involve enthalpy changes, they are often detected by calorimetric measurements . Differential scanning calorimetry has shown to effectively measure the melting temperature ( T m ) and enthalpy of homogeneous and heterogeneous DNA strands have been developed for multiplexed calorimetry, thermal insulation of a calorimeter from its surroundings becomes increasingly difficult for small samples where the surface-to-volume ratio increases.…”
mentioning
confidence: 99%